The new world of Jesus' parables - Locker, Markus (Cambridge Scholars, 2008)
Not too many other texts in biblical studies received more attention than the parables of Jesus, in fact raising the question whether or not we need yet another book on this subject. The answer to this question will always remain an emphatic yes. For Jesus and the church, the parables are mysteries, i.e. not beyond understanding, but open to an infinite possibility of meaning. This perhaps explains why more than a century after Adolf Jülicher convincingly argued for a non-allegorical reading ...